Generation of Spheres from Dental Epithelial Stem Cells - Natsiou, Despoina; Granchi, Zoraide; Mitsiadis, Thimios A.; Jimenez-Rojo, Lucia (Frontiers in Physiology, 2017)
The in vitro three-dimensional sphere model has already been established as an important tool in fundamental sciences. This model facilitates the study of a variety of biological processes including stem cell/niche functions and tissue responses to injury and drugs. Here we describe the complete protocol for the in vitro formation of spheres originated from the epithelium of rodent incisors. In addition, we show that in these spheres cell proliferation is maintained, as well as the expression of several key molecules characterizing stem cells such as Sox2 and p63. These epithelial dentospheres could be used as an in vitro model system for stem cell research purposes.